Bloodstream infections in oncology patients at Red Cross War Memorial Children's Hospital, Cape Town, from 2012 to 2014. (December 2018) - Mvalo, Tisungane; Eley, Brian; Bamford, Colleen; Stanley, Christopher; Chagomerana, Maganizo; Hendricks, Marc; Van Eyssen, Ann; Davidson, Alan
Highlights: One hundred and fifty infections occurred in eighty-nine paediatric oncology patients. Gram-positive bacteria were the main cause for bloodstream infection. Most infections occurred in haematology cancers, neutropaenia and recent chemotherapy. Fungal bloodstream infection was associated with a higher rate of complications. A low percentage of Gram-negative isolates was resistant to carbapenem antibiotics. Abstract: Objectives: This study was performed to investigate the epidemiology of bloodstream infection (BSI) in oncology patients at Red Cross War Memorial Children's Hospital (RCWMCH), Cape Town, with focus placed on the most common causes, complications, and antimicrobial susceptibilities in BSI. Methods: A retrospective cross-sectional study was conducted in the Haematology–Oncology Unit of RCWMCH. All positive blood cultures from RCWMCH oncology patients obtained in 2012 to 2014 were retrieved to identify cases of BSI. Results: Three hundred and forty-three positive cultures were identified, for 150 BSI episodes among 89 patients; 49.1% of the culture isolates were Gram-positive bacteria, 41.6% were Gram-negative bacteria, and 9.3% were fungal. Coagulase-negative Staphylococcus and viridans group Streptococcus were the most common Gram-positive isolates. Escherichia coli and Klebsiella species were the most common Gram-negative isolates. The majority of BSI episodes occurred in patients with haematological malignancies (74%), in the presence of severe neutropenia (76.4%), and were associated with chemotherapy (88%). Complications occurred in 14% of BSI. Fungal infections had the highest prevalence of complications (21.4%). Three children died during BSI, giving a case-fatality rate of 2%. Conclusions: BSI in these patients was caused mainly by Gram-positive bacteria and was associated with a low case-fatality rate. These results are consistent with worldwide experience of BSI in paediatric oncology.